2012
DOI: 10.4310/mrl.2012.v19.n3.a2
|View full text |Cite
|
Sign up to set email alerts
|

The conjugacy relation on unitary representations

Abstract: Abstract. In a 1965 paper, E.G. Effros asked the question if the conjugacy relation for unitary representations of a locally compact second countable group is a Borel equivalence relation. In this paper, we answer this question affirmatively. This also settles a recent question raised by A.S. Kechris regarding the hierarchy complexity of unitary equivalence of probability measure preserving actions of countable discrete groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…The hypothesis on Γ can be weakened considerably, and we will state our result in full in the next section. We note that Theorem 1.2 and the result of Foreman, Rudolph and Weiss stand in contrast to the recent result of Hjorth and Törnquist [16], where it is shown that conjugacy of unitary representations of any countably infinite discrete Γ is always Borel.…”
Section: Introductioncontrasting
confidence: 73%
“…The hypothesis on Γ can be weakened considerably, and we will state our result in full in the next section. We note that Theorem 1.2 and the result of Foreman, Rudolph and Weiss stand in contrast to the recent result of Hjorth and Törnquist [16], where it is shown that conjugacy of unitary representations of any countably infinite discrete Γ is always Borel.…”
Section: Introductioncontrasting
confidence: 73%
“…The details can be found in [HT12]. The theorem applies more generally to representations of locally compact second countable groups and separable C*-algebras.…”
Section: Theorem (Mackey)mentioning
confidence: 99%